2019
DOI: 10.20884/1.paju.2019.1.1.1995
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Kebugaran Jasmani Siswa SMP Di Daerah Dataran Tinggi Kabupaten Banyumas

Abstract: Kebugaran jasmani merupakan salah satu faktor penting bagi siswa untuk dapat melakukan bebagai aktivitas fisik dan olahraga, selain itu kebugaran jasmani yang baik juga dapat memberikan dampak positif terhadap perkembangan prestasi siswa, baik secara kognitif, afektif maupun psikomotor. Tujuan penelitian untuk mengetahui profil kebugaran jasmani siswa SMP di dataran tinggi Kabupaten Banyumas, khususnya di daerah Kedungbanteng dan Baturraden. Metode penelitian studi deskriptif ex-postfacto. Instrumen penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 2 publications
0
8
0
15
Order By: Relevance
“…One of the objectives of learning Physical Education and Sports is to maintain physical fitness through physical activity one of the most important aspects to maintain the stability of the body as a whole that provides the ability of the body to follow the next activity without experiencing any significant fatigue. Physical fitness in his research found that physical fitness is one of the supporting physical components to improve citation [4]- [6]. This is in line with that physical fitness is a person's physical ability to do one's activities without experiencing significant fatigue and support the stability of the body.…”
Section: Introductionmentioning
confidence: 67%
“…One of the objectives of learning Physical Education and Sports is to maintain physical fitness through physical activity one of the most important aspects to maintain the stability of the body as a whole that provides the ability of the body to follow the next activity without experiencing any significant fatigue. Physical fitness in his research found that physical fitness is one of the supporting physical components to improve citation [4]- [6]. This is in line with that physical fitness is a person's physical ability to do one's activities without experiencing significant fatigue and support the stability of the body.…”
Section: Introductionmentioning
confidence: 67%
“…Berdasarkan hasil survey tersebut, disimpulkan bahwa tingkat kebugaran dari masyarakat Indonesia termasuk siswa siswi SMA berada dalam kategori kurang. Hal ini juga didukung oleh hasil penelitain yang menyebutkan bahwa siswa SMP di dataran tinggi memiliki tingkat kebugaran yang kurang, sehingga perlu adanya program khusus untuk memicu siswa untuk melakukan berbagai aktifitas fisik dan olahraga (Kusnandar, Purnamasari, Nurcahyo, & Darjito, 2019;Suhartoyo et al, 2019) .…”
Section: Pendahuluanunclassified
“…Kebugaran jasmani merupakan salah satu faktor utama untuk dapat meraih prestasi belajar, sehingga penting bagi remaja menyediakan waktu yang cukup untuk berolahraga (Budi, 2015;Kusuma, Syafei, & Rilastiyo, 2019;Listiandi et al, 2020;Widanita et al, 2019). Aktifitas olahraga yang dimaksud adalah aktifikas olahraga yang menyenangkan dan bukan yang monoton dan membosankan (Suhartoyo et al, 2019).…”
Section: Pendahuluanunclassified
“…Covid-19 has raised public awareness about the importance of maintaining body immunity to avoid contracting viruses and diseases. They obtained excellent body immunity apart from consuming healthy, balanced, and nutritious foods and regular exercise [2]- [5].On the other hand, a pandemic condition that limits multiple activities, especially those involving many people, has caused saturation.…”
Section: Introductionmentioning
confidence: 99%